Assessing Causal Associations of Atopic Dermatitis With Heart Failure and Other Cardiovascular Outcomes: A Mendelian Randomization Study - Chen, Heng; Zhuo, Chengui; Zheng, Liangrong (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims Observational epidemiological studies have suggested that atopic dermatitis (AD) was associated with an increased risk of cardiovascular diseases (CVDs). However, causality remains to be established. In the present study, Mendelian randomization (MR) analyses were used to evaluate whether AD and CVDs are causally associated. Methods This study was based on summary statistics of genome-wide association studies (GWASs) for a set of cardiovascular outcomes including heart failure (HF), coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), stroke, and stroke subtypes. A total of 19 independent single nucleotide polymorphisms associated with AD were identified at a genome-wide significance threshold (P < 5 × 10−8) based on a large GWAS meta-analysis. MR estimates were pooled using the inverse variance weighted method. Complementary analyses further evaluated the robustness of the results. Results Genetically determined AD was causally associated with HF [odds ratio (OR), 1.07; 95% confidence interval (CI), 1.03–1.10; P = 1.11 × 10−4]. However, there was no causal association between AD and the risk of AF, CAD, MI, stroke, and stroke subtypes. Complementary analyses returned similar results. No horizontal pleiotropy was found. Conclusion This MR study provided evidence to support that AD exerted an effect contributing to HF. No significant associations were found for other cardiovascular outcomes. The study suggested that prevention and early diagnosis of AD may help prevent HF. Improved awareness of these associations is warranted for better management of CVDs in the future.